Satisfaction of Women with Labor and Delivery in Rural Punjab, Pakistan: A Cross-sectional Study - Ilyas, Nazia; Sansiriphun, Nantaporn; Nantsupawat, Apiradee; Chaloumsuk, Nonglak; Turale, Sue (Pacific Rim International Journal of Nursing Research, 2023)
Women’s satisfaction with the quality of care during pregnancy and childbirth can impact their access to and utilization of healthcare services. Since many women live in rural regions in developing nations, it is crucial to secure their access to and use of basic healthcare services to reduce maternal and newborn morbidity and mortality. This cross-sectional study is part of a first-time, sizeable, mixed-method study involving women and midwives’ quantitative and qualitative perspectives on the quality of mid- wifery care in rural Pakistan. The aim was to describe women’s satisfaction with the quality of midwifery care during labor and delivery at basic health units in rural Punjab, Pakistan. Simple random sampling was used to select 328 women from 96 basic health units. Data were collected between December 2020-March 2021. The Labor and Delivery Satisfaction Index measured women’s satisfaction with childbirth. Data were analyzed using descriptive statistics and presented in frequencies and percentages. Results indicated that the majority, 277 (84.5%), were satisfied with the quality of midwifery care during labor and delivery, whereas the remaining 51 (15.5%) were unsatisfied. Appropriate tools to monitor labor and delivery and non-pharmacological pain management during labor need much improvement. The women must also be treated with respect, given accurate information about their labor status, and given control over it. Midwives and other health service providers and administrators can use the findings of this study to improve services available to rural women.